Characterization of biochars produced from pyrolysis of pelletized agricultural residues. (October 2016) - Colantoni, A.; Evic, N.; Lord, R.; Retschitzegger, S.; Proto, A.R.; Gallucci, F.; Monarca, D.
Abstract: Biochars produced from pelletized grape vine (GV) and sunflower husk (SFH) agricultural residues were studied by pyrolysis in a batch reactor at 400 and 500 °C. Chemical and physical evolution of the biomass under pyrolysis conditions was determined and the products were characterized, including the main gaseous organic components. Results showed a decrease in solid biochar yield with increasing temperature. Biochar is defined as a "porous carbonaceous solid" produced by thermochemical conversion of organic materials in an oxygen depleted atmosphere, which has physiochemical properties suitable for the safe and long-term storage of carbon in the environment and, potentially, soil improvement. The aim of this work is to improve the knowledge and acceptability of alternative use of the biochar gained from agro-forestry biomass residuals, such as grape vine and sunflower husks, by means of modern chemical and physical characterization tools.